Nutritional Status in a Patient with Gestational Diabetes Mellitus and Pregnancy Outcome (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Both maternal nutritional status and GDM have impact on pregnancy outcome. But, data from Bangladesh in this issue is still scarce. To design and utilize national obstetric health care, nutritional status of GDM women and its impact in the birth weight of babies should be evaluated and therefore, this study was designed.Methods: This prospective cohort study was conducted in the department of Obstetrics and Gynecology at BIRDEM General Hospital-2, Dhaka to evaluate the nutritional status of GDM women and its impact on pregnancy outcomes.Results: The mean age of the patients in the study was 29.71± 5.06 years. The mean age, Mid Upper Arm Circumference (MUAC,) and Body Mass Index (BMI) were significantly higher in GDM mothers (p